PENGARUH TINGKAT KESEHATAN BANK TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS LAPORAN KEUANGAN SEBAGAI PEMODERASI - Hesti Kumala Sari; Puji Harto (Diponegoro Journal of Accounting, 2025)
This study aims to analyze  the effect of bank soundness on firm value, with financial reporting quality as a moderating variable. The dependent variable in this research is firm’s value, while the independent variable consists of bank health indicators, including risk profile, corporate governance (GCG), earnings, and capital. The moderating variable is financial reporting quality, specifically accrual quality, and control variables include firm size and firm age. The population of this study comprises banking companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sample selection method used was purposive sampling method. The result were obtain as many as 171 observations over 4 years. Data analysis was conducted using multiple linear regression in SPSS.The findings indicate that the capital has a positive effect on firm value, while GCG, earning, and risk profile do not have a significant impact on firm value. Additionally, financial reporting quality does not moderate the relationship between risk profile, GCG, earning, and capital with firm’s value.